AN ACCOUNT OF HUMAN RIGHT VIOLATIONS IN NIGERIA (PRE-BRITISH, BRITISH AND POST INDEPENDENCE) - Nwachukwu, Sunny N; Aghamelo, Austin; Stanley, Nwaneri (European Scientific Journal, ESJ, 2014)
The problem we have sought to address entails a discussion on the status and dynamics of human rights violation from British to Post Independence. We shall equally be examining the extend to which genuine democratization can resolve the hydra-headed crisis of human right abuses. At the inception of the present Fourth Republic in 1999 under the leadership of Olusegun Obasanjo, Nigerians had a sigh of relief that democracy and its twin sister, the rule of law, which is the basis for the protection of human rights, will come to stay. Unfortunately, everybody was amazed and disappointed at the level of human rights violation even in the democratic regime of Obasanjo.